VLSI implementation of AES algorithm against differential power attack and differential fault attack - HAN Jun; ZENG Xiao-yang; ZHAO Jia (Tongxin xuebao)
A VLSI implementation of AES algorithm against both differential power attack and differential fault attack was proposed. The main countermeasures employed in this hardware design are masking technique and two-dimensional parity-based concurrent error detection method. And exploits such methods as separating 128bit calculation into four 32bit calculations, module reuse and optimization of calculation order was exploited to reduce hardware cost. Moreover, a 3 level pipelined structure of AES encryption and decryption is used to improve hardware speed and throughput. The AES IP core based on these techniques can resist two kinds of side channel attacks with reasonable performance and cost.